THE ANALYSIS OF THE WORD CLASSES ACQUIRED BY TWO – FOUR YEARS OLD INDONESIAN CHILDREN IN THEIR FIRST LANGUAGE ACQUISITION - Iwan Iwan (Proceedings Education and Language International Conference, 2017)
The objectives of the research are to show other than nouns, verbs and adjectives, what the other word classes are uttered by children and also what the word class is the most frequently uttered by them in their first language acquisition. The participants of the research are five children whose age ranges from two to four years old and whose parents are native speakers of Indonesian. The conversations of the five children or subjects had with their parents in Indonesian were observed and video-recorded for two – three months. Some of the subjects also had the conversations with their auntie, brother and sister in their same native language. The subjects’ conversations were transcribed for the necessary data. The qualitative method was employed to syntactically analyze the collected data by categorizing the words uttered by the subjects into word classes or word category.The research findings reveal that the other word classes uttered by the five children or subjects of the research in their conversations are adverbs (125 words), pronouns (116 words), particles (77 words), and numerals (15 words), and that adverbs are the most frequently uttered by the subjects. Based on the above research findings, it is concluded that other than nouns, verbs and adjectives, the five subjects can also utter adverbs, pronouns, particles, numerals, and that they utter adverbs most frequently. Key Words: Word Classes, Utter, Child’s First Language Acquisition